Waste Bank Management In Waste Processing At Environmental Health Diploma Program In Magetan Campus - Frida Hendra Rinata; Tuhu Pinardi (Health Notions, 2019)
Waste problem in Magetan is harder problem. The waste occurrence rate that enters to the waste landfill site reaches ±149.15 m3/ day. Therefore, it is needed to build new management innovations to manage waste in schools and campuses.Moreover, this study aimed to describe management concept of the "Kesling Jaya" waste bank. Data collection was conducted by observation and documentation. The data analyzing techniques were data reduction, data presentation, and conclusion.The results showed that waste bank system that was found in several schools had not been implemented properly. This was due to student’s overcrowded schedule and the fact that they had not developed awareness regarding waste management by using waste bank system. Furthermore, there were 2 designs which were made for "Kesling Jaya" waste bank. Those were long-term and short-term designs. Long-term design was done by conducting training in rural areas, cities, and schools. This project was done by cooperating with lecturers through community service program while its development was collaborated with students’ cooperatives (KOPMA). The short-term design was done by implementing entrepreneurship courses into waste bank activities. The core team, lecturers and Entrepreneurship course instructors directly socialized about waste bank. Continuous socialization had an impact on student’s participation in saving at the waste bank. The success of "Kesling Jaya" waste bank was measured by using input, process, and output indicators. Input indicator involved supervisor, lecturers and instructors of Entrepreneurship courses as a companion during the implementation of the "Kesling Jaya" waste bank. The running process of waste bank system could be seen from students' participation to save in the waste bank. Output indicator was seen from the waste bank report about the number of clients and the amount of waste that was being saved that increased to be 85%. Keywords: Waste bank, Management, Waste processing